Making a success of managing and working remotely - Cook, Sarah, 1955- (Business professional collection, 2019)
This book will help managers and team members alike who are about to or have already started working remotely. It will enable managers to comprehend the challenges of managing remote workers and put strategies in place to overcome these, and will advise employees how to approach their work when doing so remotely.